THE EFFECT OF DIFFERENT pH ON THE CONCENTRATION OF SOLVED PROTEIN EXTRACT OF COLLAGENASE ENZYMES FROM ORGAN IN MALONG FISH (Congresox talabon) - Wikky Aditiya Putra; Rahman Karnila; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to determine the concentration of dissolved protein contained in the crude extract of the collagenase enzyme from the internal organs of malong fish (Congresox talabon) based on different pH. The research was carried out through the process of sample preparation, collagenase enzyme extraction, and measurement of dissolved protein concentrations in crude extracts of collagenase enzymes based on different pH. The results showed that the malong fish had a proportion of 55% meat, 25% bones, 8% offal-gonads, and 12% skin. The concentration of dissolved protein in crude extract of collagenase enzyme at pH 6.5; 7.5; 8.5 respectively of 5.53 ± 0.02 mg / ml, 6.08 ± 0.04 mg / ml, and 6.94 ± 0.05 mg / ml. Increasing the pH value can increase the concentration of dissolved protein in the crude extract of the collagenase enzyme from the internal organs of malong fish.Keywords: Congresox talabon, collagenase enzymes, malong fish, protein